2018
DOI: 10.13057/biodiv/d200124
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Further morphological evidence for separating Mukia Arn. from Cucumis L.

Abstract: Pratami, MP Chikmawati T, Rugayah. 2019. Short Communication: Further morphological evidence for separating Mukia Arn. from Cucumis L.. Biodiversitas 20: 211-217. Mukia Arn. is closely related to Cucumis L. based on molecular data, nevertheless, they have high morphological differences resulting in different opinion on taxonomical status of the two genera. Mukia Arn. has many similarities in pollen and leaf anatomical characters to Cucumis L., but both genera differ in seven seed characters, i.e color, shape, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Examination of morphological characterization within genotypes showed a wide variation of genotypes in terms of morphological characteristics (plant, flower, fruit, leaf). In many studies of Cucurbitaceae family, it has been emphasized that diversity is high in terms of morphologic characteristics 40 – 43 . In a similar study by 8 , it has been determined that pumpkin genotypes showed high diversity in terms of fruit characteristics 44 have showed that major color of the skin was yellow in 21 (24%) pumpkin genotypes green in 2 (2%), green-yellow grayish in 15 (18%), dark yellow -green grayish in 22 (27%), light yellow in 17 (21%) and dark yellow in 4 (5%).…”
Section: Discussionmentioning
confidence: 99%
“…Examination of morphological characterization within genotypes showed a wide variation of genotypes in terms of morphological characteristics (plant, flower, fruit, leaf). In many studies of Cucurbitaceae family, it has been emphasized that diversity is high in terms of morphologic characteristics 40 – 43 . In a similar study by 8 , it has been determined that pumpkin genotypes showed high diversity in terms of fruit characteristics 44 have showed that major color of the skin was yellow in 21 (24%) pumpkin genotypes green in 2 (2%), green-yellow grayish in 15 (18%), dark yellow -green grayish in 22 (27%), light yellow in 17 (21%) and dark yellow in 4 (5%).…”
Section: Discussionmentioning
confidence: 99%
“…(Nikmah et al 2020) and Cucumis sp. (Pratami et al 2019). So far, the most popular salak in the market is salak with white arillus especially in species Salacca zalacca, while red arillus is thought to have many properties and is useful for humans (Yuliamita 2014;Saleh et al 2018;Fendiyanto et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the same species but having two different kinds of characteristics, it can be said that these characters are included in the subspecies distinguishing features. Determination of subspecies differentiating features can be supported by morphological, anatomical, molecular, or metabolite approaches (Yuliamita 2014;Harahap and Ardiarini 2018;Zhang et al 2018;Pratami et al 2019;Satrio et al 2019;Nikmah et al 2020;Fendiyanto et al 2020). Determining the distinguishing features of the arillus in S. sumatrana has its challenges due to different physiological factors.…”
Section: Introductionmentioning
confidence: 99%
“…The secondary metabolites in C. hirta can investigate narrowly down to understand the mechanism of the interaction between their extract and growth of microbes, especially using biological markers. Biological marker in some species can be divided into several markers, i.e., morphological (Pratami et al 2019), genetic (Satrio et al 2019;Pratami et al 2020;Miftahudin et al 2021), physiological (Andriyanto and Fendiyanto 2019;Miftahudin et al 2021), and metabolite markers Fendiyanto et al 2021).…”
Section: Discussionmentioning
confidence: 99%